Óleos essenciais como anestésicos em serrasalmídeos e expressão gênica de genes relógio e das enzimas digestivas em jundiá - Almeida, Ana Paula Gottlieb (2018)
Anesthetics of synthetic origin are widely used in aquaculture to minimize animal stress arising from the practices involved in this activity. However, the adverse effects caused by these synthetic substances have encouraged research for natural substances with sedative and anesthetics properties that are more effective, safer and with lower risk of adverse effects. Studies have shown that essential oils (EOs) extracted from the plants species Aloysia triphylla and Lippia alba, as well as eugenol, an isolated compound of clove oil, present sedative and anesthetic properties in fish, being considered promising alternatives to traditional anesthetics. In this context, the first part of this study aimed to investigate the effects of these EOs on two Amazonian species, Serrasalmus rhombeus and S. eigenmanni, inhabitantsof Rio Negro. In the second part, we evaluated the gene expression of clock and digestive enzymes genes in post-larvae and juvenile of Rhamdia quelen. In the article 1, the sedative and anesthetic efficacy of A. triphylla and L. alba EOs and eugenol and the recovery time was determined in Serrasalmus rhombeus, as well as the swimming behavior on a short exposure of 15 min at low concentrations to evaluate the possible use of these substances in the transport of this species. Both EOs and eugenol are effective, with concentrations of 150, 200, and 50 μL L-1, respectively, being recommended for anestesia. For sedation, it is recommended to use 50 μL L-1 for both EOs and 25 μL L-1 for eugenol. The concentrations of 5 and 10 μL L-1 are indicated for transport studies with these anesthetics. In manuscript 2, the sedative and anesthetic efficacy of A. triphylla and L. alba EOs in Serrasalmus eigenmanni, as well as recovery time of the fish were determined. The net ion fluxes, blood parameters, and swimming behavior at a prolonged exposure of 4 h were also evaluated. Both EOs were effective for anesthesia of S. eigenmanni and the concentration of 100 μL L-1 was recommended for both EOs. For sedation, the indicated concentrations are 25 and 50 μL L-1 of A. triphylla and L. alba EOs, respectively. For transport, the concentration of 5 μL L-1 of A. triphylla EO is recommended due to the lower ammonia excretion and maintenance of fish equilibrium. In post-larvae, genes of the positive loop (artnl1a and clock) and the negative loop (per1,2,3 and cry1,2) presented differences in expression levels throughout the evaluated period, with acrophase occurring in the same schedule. In juveniles, only one positive loop gene (arntl1) and one negative loop gene (cry2) showed differences in expression levels in the evaluated period, with a difference of 1 h between the acrophases. The levels of gene expression of the digestive enzymes in post-larvae were maximal 4 h before feeding and at least 1 h after feeding. In the digestive tract of juveniles the levels of gene expression of the digestive enzymes did not differ in the evaluated period. In conclusion, both OEs are effective for sedation and anesthesia of S. rhombeus and S. eigenmanni, and may also be used in transport studies for these species. Both post-larvae and juveniles did not exhibit the typical interaction between the genes of the positive (arntl and clock) and negative (per and cry) loops and only in post-larvae the gene expression of the digestive enzymes is probably influenced by the genes clock.